(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
In the tourism sector, cultural identity is crucial, particularly in the field of tourism architecture. Because it allows visitors to sense and experience local culture firsthand, tourism architecture that represents cultural identity can be a big draw. Additionally, local communities might gain economically and socially from tourism architecture that enhances cultural identity. The significance of using tourism architecture to create cultural identity, traits of such architecture that reflect cultural identity, successful examples of such architecture, the idea of sustainable tourism architecture to preserve cultural identity, and the role of architects in fostering cultural identity through tourism architecture, challenges in using tourism architecture to create cultural identity, government interests in using tourism architecture to promote cultural identity, the benefits of using tourism architecture to create cultural identity for local communities. This study employs a qualitative descriptive approach to analyze the relationship between tourism architecture and cultural identity. Data were collected through a combination of literature review, case study analysis, and comparative evaluation of selected tourism architectural projects that successfully integrate cultural elements. The findings from these multiple sources are synthesized to develop recommendations for applying tourism architecture as a tool for strengthening and preserving cultural identity in sustainable tourism development.